Customer Behaviour Analysis with AI Implementation at Banks Operating in Azerbaijan - Abbasova, Gunay (ADA University, 2022)
The technological disruption is redefining the industries and altering the way commercial establishments operate, and each are of business is evaluating selections and implementing ways in order to make value in the innovative world. Since we entered fourth industrial revolution,, machine-learning and artificial intelligence innovation are powering automation of business in progressively much more sectors, from scheming optimum transport loads to sifting loan applicants less of the human contribution. One of the foremost industries being impacted by these alterations is banking segment, which is experiencing revolutionary vicissitudes, the most imperative of them being the upsurge in customer centeredness. This research aims to examine the customer behaviour analysis with artificial intelligence implementation at the banks functioning in Azerbaijan. In doing so, this research explores the existing literature on the AI and banking sector, analyses the AI implementations of the banks operating in Azerbaijan, and studied the ways customers react to these implementations. This research utilizes the compounds of the theorical and empirical research methods. As such, there will be survey-based primary research, which will aim at understanding and describing the approaches of the bank customers in Azerbaijan to the AI-powered applications and solutions of the banks. In addition to this, there will be structured interviews with the IT departments of large banks operating in Azerbaijan, with the aim of understanding which AI applications they currently utilize, and what are the benefits and challenges of implementing them.
Keywords: Customer behaviour; Customer behaviour analysis; Banking sector; Artificial intelligence; Digital tools; Business